The Methodology of Developing the Urban Heat Island E-module on the Achievements and Collaboration Skills of High School Students in Surakarta - Siti Azizah Susilawati; Mohd Hairy Ibrahim; Nor Kalsum binti Mohd Isa; Norwaliza Abdul Wahab; Muhammad Musiyam; Agus Herianto; Nurin Rochayati (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
Nowadays, Urban Heat Island (UHI) occurs in big cities worldwide. The UHI phenomenon needs to be introduced in school because this phenomenon occurs around the students. Surakarta, one of the big cities in Indonesia, has been threatened by the UHI phenomenon, so enrichment materials related to the UHI phenomenon are needed for students in schools. This research will develop the UHI e-module as an enrichment teaching material on the impact of global climate change and research on climate and its utilization. This paper aims to present an e-module development research methodology on UHI based on the phenomenon of UHI threats in Surakarta City and its effect on student achievement and collaboration skills. Design and Development Research (DDR) uses the Borg and Gall model. The methodology of the research development is divided into three phases: the needs analysis phase, the design and development phase, and the implementation and evaluation phases. The difference in this research is the geographical space-based study approach in the development of material based on the UHI phenomenon in Surakarta City and urban and rural spatial sampling techniques.